The effect of mimosa and syntan mixture on the quality of tanned red snapper leather - Pratama, Megadian; Sahubawa, Latif; Pertiwiningrum, Ambar; Rahmadian, Yudi; Puspita, I D (2017)
This study aimed to determine the effect of syntan and mimosa combination on the quality of tanned red snapper leather. The study was designed using complete randomized design (CRD) and the advanced test of Least Significant Difference (LSD) with three replications and three treatments of combined syntan and mimosa, namely: p1 (4 % syntan, 5 % mimosa), p2 (8 % syntan, 5 %mimosa), p3 (12 % syntan, 5 % mimosa). Data were analyzed using SPSS 18. The measured parameters were tensile strength (N·cm ), elongation (%), tear strength (N·cm -2 ), enervation (mm), wrinkle temperature (°C), fat/oil content (%) and water content (%). The results indicate that the combined syntan and mimosa tanners gave no significant effect on the physical parameters (tensile strength, elongation, tear strength, enervation and wrinkle temperature) and chemical parameters (moisture and fat/oil). All treatments (p1, p2 and p3) met the Indonesian National Standard (SNI) 06-4586-1998 for chrome tanned freshwater snake leather for the parameters of tensile strength, tear strength, enervation, wrinkle temperature and moisture. The parameter of elongation and fat/oil content did not meet with the SNI 06-4586-1998. Among the three combinations of a tanner, syntan 4 % and mimosa 5 % treatment gave the best leather quality.